Effect of Condensed Tannins containing Guava Leaf Meal on Feed intake, Feed Conversion Ratio, Carcass Characteristics and Economics of Broiler Chicks - Daing, M. I.; Pathak, Anand Kumar; Sharma, R. K.; Zargar, M. A. (Indian Journal of Animal Nutrition, 2020)
Present study was undertaken in 120 day-old unsexed broiler chicks. They were randomlydistributed into 4 dietary treatments (T1, T2, T3 and T4 supplemented with guava leaf meal (GLM) @ 0, 1, 2 and 4 % of diet, respectively) of 30 birds per group, each having 3 replicates (10 birds per replicate) in a complete randomized block design (CRD) to evaluate the effect of condensed tannins (CT) containing guava leaf meal (GLM) supplementation on feed intake, feed conversion ratio (FCR), carcass characteristics and economics of broiler chicks. Cumulative feed intake in 0-3, 0-6 and 4-6 weeks of broiler chicks were significantly (P